1986
DOI: 10.3109/00365528608996414
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Peritoneal Proteolysis and Hemodynamics of Prophylactic Infusion with CI Inhibitor in Experimental Acute Pancreatitis

Abstract: Acute pancreatitis was induced in pigs by manual retrograde injection of Na-taurocholate into the pancreatic duct. Chromogenic peptide substrate assays showed increased trypsin (TRY) and plasma kallikrein activities (KK), parallel with a reduction of prekallikrein (PKK) levels and functional plasma kallikrein inhibition (KKI), in the peritoneal exudate in untreated animals. Pretreatment with C1 inhibitor (C1 INH) concentrate significantly increased the KKI capacity, parallel with unchanged KK and TRY activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
6
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
5
6
0
Order By: Relevance
“…Likewise, leukocyte sequestration in the lungs, as assessed by MPO activity, was decreased by sCR1. These findings are in agreement with other studies (15,23,34) indicating a possible therapeutic role of complement inhibition in the setting of acute pancreatitis. However, two recent studies (2, 31) that could not confirm these beneficial effects applied the model of mild cerulein-induced pancreatitis.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Likewise, leukocyte sequestration in the lungs, as assessed by MPO activity, was decreased by sCR1. These findings are in agreement with other studies (15,23,34) indicating a possible therapeutic role of complement inhibition in the setting of acute pancreatitis. However, two recent studies (2, 31) that could not confirm these beneficial effects applied the model of mild cerulein-induced pancreatitis.…”
Section: Discussionsupporting
confidence: 83%
“…Complement inhibition by the C1 esterase inhibitor has been proven effective in the treatment of experimental severe pancreatitis (23,34). Supporting these results, complement inhibition by the recombinant soluble complement receptor 1 (sCR1) attenuated leukocyte-endothelium interaction and preserved endothelial barrier function in ischemia-reperfusion injury of the pancreas (28).…”
supporting
confidence: 53%
“…The ischemic pancreas, being a source of controversial myocardial depressant factor MDF [8,10,11], may cause the cardiac depression and aggravate the state of shock. The present study confirms hemodynamic consequences in experimental pancreatitis, delivered by other authors [2,3,5,12,13] although they are quite different from hemodynamic data obtained in patients in clinical conditions [8,14]. Untreated animals developed a progressive circulatory insufficiency: the decrease of cardiac output, mean artery pressure, and left ventricular stroke volumne.…”
Section: Discussionsupporting
confidence: 57%
“…Similarly, Ruud et al [5], using C1 inhibitor durOffprint requests to: Marek Dobosz, MD ing their studies, demonstrated the improvement of survival rate and hemodynamic performance in experimental acute pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental studies from our laboratory have shown that intravenous ad ministration of both Cl-Inh and aprotinin improves hemodynamics and survival rates in taurocholate-induced pancreatitis [28]. Such effects are also seen after corticosteroid pretreatment in the same experimental model on acute pancreatitis [29].…”
Section: Discussionmentioning
confidence: 56%